Challenges in Implementation of Digital Culture Environment among Rural Community in Malaysia: An Overview - Tokiran, Nurul Syfa’ Mohd; Hussin, Norhayati; Shahibi, Mohd Sazili (Journal of Asian Scientific Research, 2021)
The purpose of the article is to assess the current challenges in the implementation of the Digital Culture Environment among the rural community in Malaysia. The Covid-19 pandemic has changed the online environment where a drastic usage of digital tools has been observed among Malaysian. The digital culture is defined as the culture shaped by the emergence of digital technologies and their usage in the community. The literature survey approach has been applied as the methodology of study to explore the current challenges in the implementation of the Digital Culture Environment among the rural community in Malaysia. Several challenges have been identified, including the rural sustainable issues, digital divides, demographic factors, Information, Communication and Technology (ICT) factor, individual, as well as behavior factor. According to the literature review conducted, these challenges have been revealed to significantly hurdle the government’s movement in implementing the digital culture within the rural community. To overcome these challenges, a strong and effective supporting model should be formulated to assist the government in building and establish a digital culture environment in Malaysia, particularly among the rural community. Hence, a further in-depth study is required to acquire comprehensive literature information to address this issue.